2001
DOI: 10.1080/14616700118394
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Global Journalist: a hierarchy-of-influences approach

Abstract: Globalization of media organizations has brought accompanying debates about the proper education and professional standards for the journalists who work for them. These journalistic and press performance issues have attracted a correspondingly global community of scholars to conduct often transnational, comparative studies. In this article, I consider the issues raised in examining these "global journalists" from a sociology-of-media and a cross-national comparative perspective. I propose a "hierarchy of in ue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
182
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(193 citation statements)
references
References 14 publications
5
182
0
6
Order By: Relevance
“…It is well known that newspapers are influenced by their environment including ownership, funding, need for circulation, advertisement revenue and the readers preference for reading like-minded news (Abbring & Van Ours, 1994;Allport & Faden, 1940;Anderson, 2009;Bulkow, Urban, & Schweiger, 2013;Carragee & Roefs, 2004;Gentzkow & Shapiro, 2010;George, 2007;Gilens & Hertzman, 2000;Illia, Lurati, & Casalaz, 2013;McCauley, Blake, Meissner, & Viswanath, 2013;Price, 2003;Reddaway, 1963;Reese, 2001;Roberts & McCombs, 1994;Schudson, 2002;Shoemaker, Vos, & Reese, 2009;Sill, Metzgar, & Rouse, 2013;Weaver & Elliott, 1985;White, 2013;Winseck, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that newspapers are influenced by their environment including ownership, funding, need for circulation, advertisement revenue and the readers preference for reading like-minded news (Abbring & Van Ours, 1994;Allport & Faden, 1940;Anderson, 2009;Bulkow, Urban, & Schweiger, 2013;Carragee & Roefs, 2004;Gentzkow & Shapiro, 2010;George, 2007;Gilens & Hertzman, 2000;Illia, Lurati, & Casalaz, 2013;McCauley, Blake, Meissner, & Viswanath, 2013;Price, 2003;Reddaway, 1963;Reese, 2001;Roberts & McCombs, 1994;Schudson, 2002;Shoemaker, Vos, & Reese, 2009;Sill, Metzgar, & Rouse, 2013;Weaver & Elliott, 1985;White, 2013;Winseck, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Next is the extramedia level, where such elements as public relations and advertising contribute to newsmaking. Finally is the ideological level, where meaning conveyed in media messages is usually mobilized in the service of power thereby letting particular ideologies thrive over others (Reese, 2001).…”
Section: The Media-ideology Interfacementioning
confidence: 99%
“…We should recognize that certain coverage characteristics, such as political violence labeling, alerts us to the control process behind the control practiced by media per se. In other words, both the extramedia and ideological levels of influence within the hierarchy-of-influences upon newswork (Reese, 2001) come into play here. These levels underline the notion that media institutions are not the sole creators of news.…”
Section: Multilayered Influence On Media Contentmentioning
confidence: 99%
“…It is well known that journalists influence media delivery and also often set agendas and that journalists are influenced by their environment (Allport & Faden, 1940;Bulkow et al, 2013;Carragee & Roefs, 2004;Illia et al, 2013;McCauley et al, 2013;Reese, 2001;Shoemaker et al, 2008;Sill et al, 2013;Tilley & Hollings, 2008;Weaver & Elliott, 1985). Ahchong and Dodds and Liu found that the regional newspapers they investigated (Toronto Star and Houston Chronicle) both covered little local and regional content but mostly national and International content related to climate change (Ahchong & Dodds, 2012;Liu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately the other local newspapers that are distributed in Calgary and Edmonton who have a different ownership are not available through the Canadian Newsstand database or another database available to us. News generated is also influenced by context outside the media organization (Reese, 2001). We have chosen two newspapers from a Canadian province that heavily depends on energy production.…”
Section: Limitationsmentioning
confidence: 99%